Dune. House Harkonnen. Volume two - Herbert, Brian; Anderson, Kevin J., 1962- (BOOM! Studios, 2024)
"Spanning from Arrakis to Wallach IX, formative moments from major characters' past in the Dune universe come to light driven by the ruthless machinations of House Harkonnen! Chaos ensues across planets with tense rescue missions, impossible choices, meanwhile events on Ix turn explosive, and Bene Gesserit plotting finally comes to fruition. As the Harkonnens brutality abounds on Arrakis, Liet and Warrick are pitted against each other in the name of love, Leto finds himself in a fateful meeting elsewhere, and Duncan takes a significant step toward who he's destined to be... "--Amazon.